Fractional electrical dynamics in fruits and vegetables - Jesus, Isabel S. (2019)
Fractional calculus (FC) was originally developed in a pure mathematical viewpoint. However, nowadays FC is applied in many emerging fields of physics and engineering. This paper studies the fractional electrical impedance of vegetables and fruits having FC modelling in mind. In this line of thought, are developed several experiments for measuring the impedance of botanical elements, based in the Bode and polar diagrams. An electrical circuit that models these systems is presented and conclusions are drawn.